Economic Feasibility of Functional Meat Products for Commercial Production in India - Varalakshmi Kandanuri (Turkish Journal of Agriculture: Food Science and Technology)
This paper analyses the production of functional chicken meat products from economic perspectives. It analyses and compares the economics and investment feasibility on different size groups of processing plants in India. The primary data on input use and output yield were taken from studies of NRCM and data was analysed using economic analysis and investment appraisal techniques like NPV, IRR(%), BC ratio, and Break even analysis. The results indicated that the cost of production of functional products was 5.2 and 5.18 and 4.59 US dollars per kg on small, medium and large scale units respectively. All the processing units are found to be economically feasible with NPV of US$ 12727, 64661 and 153703, IRR of 26%,31% and 42% and B-C ratio was estimated as 1.56, 1.78 and 2.29 for small, medium and large scale units respectively. Economies of scale is evident form all perspectives like production costs, profits, discounting measures and breakeven point. The study found the feasibility of functional meat products in India for commercial production.